Análise crítica de dispositivo em projetos de lei da Câmara dos Deputados do Brasil (2013-2023) que tratam sobre ideologia de gênero - Nascimento, Brunna Felkl do (2024)
The discourse on gender ideology appears in the late 1990s, through Catholic discourses, such as subversion and criticism of gender studies, it takes over the international scene and is inserted in Brazilian politics through anti-democratic discourses and political projects. From 2013 to 2022, 39 Bills dealing with the subject were proposed in the Chamber of Deputies/Brazil by Deputies from parties focused on the new right/extreme right. The present research develops a critical analysis of discourses and devices to describe the devices operated in the discourses on gender ideology present in the Bills of the Chamber of Deputies/Brazil (2013-2022) that deal with the subject and analyze how they seek control over knowledge and population behavior with regard to gender norms. From the thought of Michel Foucault, who understands the device as a methodological instrument for understanding the networks between discourses, institutional practices and effects of power, the research presents two hypotheses: (b) The bills use moral panic as a governmentality device of the extreme right / Brazil (2013-2022), with regard to gender norms, in search of control over the behavior and knowledge of the subjects.